2021
DOI: 10.1186/s12880-021-00656-7
|View full text |Cite
|
Sign up to set email alerts
|

An artifıcial ıntelligence approach to automatic tooth detection and numbering in panoramic radiographs

Abstract: Background Panoramic radiography is an imaging method for displaying maxillary and mandibular teeth together with their supporting structures. Panoramic radiography is frequently used in dental imaging due to its relatively low radiation dose, short imaging time, and low burden to the patient. We verified the diagnostic performance of an artificial intelligence (AI) system based on a deep convolutional neural network method to detect and number teeth on panoramic radiographs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Several studies have reported that artificial intelligence helps in image reading, and that it helps clinicians 20,21 . In the field of dentistry, artificial intelligence research using panoramic photos has been actively conducted recently; most studies have been on tooth segmentation and tooth number matching [22][23][24] , detection of primary teeth 25 , and detection of taurodontism 26 , which is a tooth anomaly. Studies on artificial intelligence detection of osteoporosis in panoramic photos are also being actively conducted [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that artificial intelligence helps in image reading, and that it helps clinicians 20,21 . In the field of dentistry, artificial intelligence research using panoramic photos has been actively conducted recently; most studies have been on tooth segmentation and tooth number matching [22][23][24] , detection of primary teeth 25 , and detection of taurodontism 26 , which is a tooth anomaly. Studies on artificial intelligence detection of osteoporosis in panoramic photos are also being actively conducted [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Bilgir et al [ 19 ] developed a Faster R-CNN to automatically number teeth on a database of 2,482 panoramic radiographs. This study achieved a precision of 0.9652.…”
Section: Discussionmentioning
confidence: 99%
“…However, although these models have good performance in detecting abnormalities, they cannot recognize tooth numbers to provide detailed diagnostic information on individual teeth, therefore limiting the clinical application of these DL models. Recently, some DL models were developed to segment teeth [22], detect and assign tooth numbers on dental radiographs [23][24][25][26][27], diagnostic charting [28], or detect and classify each tooth into molar, premolar, canines, and incisors [29,30]. However, all of them were only applicable to panoramic radiographs [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some DL models were developed to segment teeth [22], detect and assign tooth numbers on dental radiographs [23][24][25][26][27], diagnostic charting [28], or detect and classify each tooth into molar, premolar, canines, and incisors [29,30]. However, all of them were only applicable to panoramic radiographs [22][23][24][25][26][27][28][29][30]. Furthermore, some studies have been conducted on detecting teeth and assigning tooth numbers in periapical radiographs [6,31,32] and bitewing radiographs [33,34].…”
Section: Introductionmentioning
confidence: 99%